Oxymatrine Inhibits Renal Cell Carcinoma Progression by Suppressing β-Catenin Expression - Jin, Yinshan; Liu, Jiannan; Liu, Yadong; Liu, Yang; Guo, Guiying; Yu, Shiliang; An, Ruihua (Frontiers in Pharmacology, 2020)
Aims: Oxymatrine (OMT) has been identified to possess immunomodulatory, anti-inflammatory and anti-cancer properties. This study aimed to investigate its precise function and the underlying molecular mechanisms in renal cell carcinoma progression. Methods: The antineoplastic effect of oxymatrine was investigated by CCK-8 assay, cell cycle analysis, apoptosis assay, wound healing experiment, transwell assay and drug-sensitivity analysis in renal cancer cells following oxymatrine treatment. The modulation of oxymatrine on β-catenin was analyzed through western blot and immunofluorescence assay. β-catenin overexpression was employed to determine the key role of β-catenin in oxymatrine-inhibited renal cell carcinoma in vitro. In addition, animal model was established to investigate the effect of oxymatrine on tumor growth in vivo. Results: Oxymatrine inhibited renal cell carcinoma progression in vitro, including cell proliferation, apoptosis, migration, invasion and chemotherapy sensitivity. Further mechanistic studies demonstrated that oxymatrine exerted its antineoplastic effect through suppressing the expression of β-catenin. Moreover, in nude mice model, oxymatrine exhibited remarkable inhibition of tumor growth, which was consistent with our in vitro results. Conclusions: Our findings illuminate oxymatrine as an effective antitumor agent in renal cell carcinoma, and suggest it a promising therapeutic application in renal cell carcinoma treatment.